Hierarchical Porous g-C3N4 as a Photocatalyst Nanomaterial - Aryswan, Adhe (Journal of Research and Development on Nanotechnology, 2021)
Heterogeneous photocatalysts are in the spotlight recently, due to the rises of environmental pollution and energy crisis. Graphitic carbon nitride (g-C3N4) material shows a potential photocatalyst with attractive properties such as metal free, low band gap, and high stability. However, the bulk g-C3N4 photocatalytic performance is unsufficient to be work properly in the practical applications. Hierarchical porous nanostructure is one of modification that could be applied to improve the photocatalytic activity. This review discusses the g-C3N4 material as a promising photocatalyst, including other potential modifications to improve its photocatalytic performance